Vulnerability Analysis of Andalas University Library Building Using Microtremor HVSR Method - Pohan, Ahmad Fauzi; Putri, Yunita; Algusduri, Nopra; Islami, Keisyah Putri; Fitri, Intan; Fiona, Gusti; Deshafa, Abdul Fadhila; Fajri, Rahmad; Erawati, Yuni; Rahmah, Rika Amalya; Jannah, Azani; Nanda, Fauzan Surya; Zai, Febriwati (Journal of the Physical Society of Indonesia, 2025)
This research aims to analyze the vulnerability of the Andalas University Library UPT Building which is located in an earthquake-prone area using the microtremor HVSR method. Measurements were taken at 20 points on each floor of the building to determine the natural frequency value, amplification factor, and seismic vulnerability index. The results show that the natural frequency values have a stable distribution pattern on most floors, with small variations on certain floors due to mass distribution or structural stiffness. The highest amplification values were found on floors 2 and 3, indicating the potential for local resonance. The highest seismic vulnerability index is on floor 2 with values up to 750, indicating the need for more attention to the design and structural strength of that floor. The HVSR method proved effective in analyzing the dynamic characteristics and potential vulnerability of buildings to earthquakes, providing important information for risk mitigation in disaster-prone areas.